Musyarakah Mutanaqisah as a Financing Solution for Working Capital and Productive Property in Islamic Financial Institutions in Indonesia - Putri Tri Cahyani; Rizaludin; Yadi Janwari (Mabahits Al-Uqud, 2024)
This study examines the implementation of Musyarakah Mutanaqisah (MMQ) as a financing instrument for working capital and productive property in Islamic Financial Institutions (IFIs). Unlike conventional financing, MMQ offers a dynamic ownership transition mechanism that allows customers to gradually acquire full ownership of financed assets while sharing profits and risks with the bank. The research employs a qualitative approach through an analytical review of scholarly literature and publications from IFIs, focusing on the operational structure, benefits, and challenges of MMQ. The findings highlight that MMQ provides greater flexibility compared to other Sharia-compliant contracts such as Murabahah and Ijarah Muntahiyah Bi Tamlik, as it enables customers to secure assets while mitigating financial burdens through staged payments. MMQ proves to be a viable solution for business actors and property investors, offering an equitable risk-sharing model and a structured path toward ownership. The study also underscores the importance of financial literacy and strategic marketing in enhancing MMQ adoption, emphasizing the role of digital platforms and personalized consultation in promoting its benefits. The results suggest that optimizing MMQ for productive financing can strengthen the Islamic banking sector and expand financial inclusion for businesses. Further empirical research is needed to measure MMQ’s long-term impact on business sustainability and financial stability.